(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This article presents a definition for the term Extended School Day Policies (PAJE – Brazilian acronym for Políticas de Ampliação da Jornada Escolar) and five terms that are used in the research on this theme, namely, a) Full-time School; b) Extended School Day; c) Integral Education; d) Full-time Education; and e) Full-time Integral Education. The terminology characterization was defined from the listing of 704 theses and dissertations on PAJE, presented between 1992 and 2019. It was concluded that: a) there is a variety of terms, which are not always used consistently in the research reports; b) clarifying the terminology might contribute to more coherent research; and c) the span of the term PAJE allows it to incorporate the variety of themes that have been explored in the research on extending the time destined to educate children and adolescents at school. Keywords: Education Policies. Integral Education. Extended School Day.